2020
DOI: 10.3390/ijerph17238774
|View full text |Cite
|
Sign up to set email alerts
|

Costing the Scale-Up of a National Primary School-Based Fluoride Varnish Program for Aboriginal Children Using Dental Assistants in Australia

Abstract: There is good evidence that fluoride varnish programs are effective in preventing dental caries in children. This study aims to provide a costing for the scale-up of a child fluoride varnish program in New South Wales (NSW), Australia. Most child fluoride varnish programs are school-based, and a number of studies have examined the acceptability and cost effectiveness of using non-dental providers to apply the fluoride varnish. This paper describes the number of primary schools in Australia that could be target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Similar approaches in the Northern Territory, 34 Western Australia 35 and Tasmania 36 have also used paraprofessionals, including Aboriginal Health Workers, for fluoride varnish application programs. The success of the fluoride varnish program in New South Wales has resulted in a call to scale up the initiative to a state‐wide program 37 . No comparable programs are currently underway in South Australia, but the existing evidence‐base suggests that a similar approach is not only feasible but could be quite successful in minimising the experience of dental caries, particularly for children 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar approaches in the Northern Territory, 34 Western Australia 35 and Tasmania 36 have also used paraprofessionals, including Aboriginal Health Workers, for fluoride varnish application programs. The success of the fluoride varnish program in New South Wales has resulted in a call to scale up the initiative to a state‐wide program 37 . No comparable programs are currently underway in South Australia, but the existing evidence‐base suggests that a similar approach is not only feasible but could be quite successful in minimising the experience of dental caries, particularly for children 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Wales has resulted in a call to scale up the initiative to a state-wide program. 37 No comparable programs are currently underway in South…”
Section: Oral Health and Nutrition Information Shared Onlinementioning
confidence: 99%
“…The greater use of the fluoride varnish items for programs targeting Aboriginal and Torres Strait Islander may also increase utilisation of the CDBS, which has been particularly low for Aboriginal and Torres Strait Islander children. If dental assistants were also able to claim for fluoride varnish services under the CDBS, this would further improve cost effectiveness while also reducing pressure on oral health services where there are shortages of dental and oral health practitioners [31].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, fluoride varnish application is restricted to dental professionals in SA, despite its value in preventing ECC [85]. Researchers in New South Wales have successfully demonstrated that Indigenous dental assistants can effectively and safely apply fluoride varnish for children in schools; these findings have the potential to better oral health for Indigenous children across Australia [86].…”
Section: Child-level Influencesmentioning
confidence: 99%